Cyanoacrylate tissue glue for wound repair in early posttrabeculectomy conjunctival bleb leak: a case series - Abdul Rahim, Haslinda; Yaakub, Azhany; Rasid, Noor Khairul; Embong, Zunaina; Ahmad Tajudin, Liza Sharmini (Dove Medical Press, 2015)
We demonstrated a noninvasive management of early bleb leak following trabeculectomy using cyanoacrylate tissue glue (CATG). Three patients who underwent augmented trabeculectomy with mitomycin C with early bleb leak between January 2009 and June 2010 were reviewed. Case 1 and Case 2 exhibited bleb leak on postoperative Day 1 and Case 3 showed leak on follow-up at postoperative Day 7. Case 1 was successfully sealed with CATG at postoperative Day 3, after failed pressure padding and bandage contact lens. Case 2 was successfully sealed with CATG at postoperative Day 3, after failed pressure padding and conjunctiva flap resuturing. In Case 3, the leaking conjunctival flap was managed with combined techniques of resuturing and applying CATG at postoperative Day 9, after failed pressure padding. During leakage, the intraocular pressure was low (6–8 mmHg) in all three cases, with shallow anterior chamber depth and absence of other complications such as choroidal detachment, hypotony maculopathy, or endophthalmitis. Foreign body sensation was the main complaint following the procedure. No clinical allergy reaction was documented. CATG may serve as a potential adjunctive and effective method in the management of posttrabeculectomy early bleb leak.